Asthma induced by ivory dust: a new occupational cause. Issue 9 (September 1988) - Armstrong, R A; Neill, P; Mossop, R T
Abstract : A case of asthma is reported that was due to ivory from the tusk of the elephant, a cause of occupational asthma unique to Africa.